Phononic band-gaps of Hoberman spherical metamaterials in low frequencies - Yangbo Li; Siyu Cao; Yan Shen; Yongdong Meng (Materials & Design, 2019)
Periodically engineered structures, having the capability to manipulate mechanical wave propagation and exhibiting omnidirectional phononic band gaps, are important for various potential applications such as wave filtering, waveguiding, acoustic cloaking, thermal management, and energy harvesting. In natural materials, vibration mitigation capability depending on inherent damping feature usually cannot be adjusted easily and broad attenuation frequency ranges are still uncommon in these materials. Here, inspired by the Hoberman sphere architecture, we propose a novel lattice system with broad and multiple omnidirectional phononic band gaps, which are attributed to the local resonances mechanism. Guided by numerical simulations, analytical formulations, and low amplitude transmission testing, we show that the proposed lattice metamaterials can exhibit broad and multiple omnidirectional band gaps over a wide range of node connectivity and constituents. The finding reported here provides a new routine to design phononic metamaterial systems with tunable band gaps, offering a wide range of potential applications in harsh environmental conditions. Keywords: Phononic crystals, Metamaterials, Lattice, Vibration control, Band gaps, 3D printing